A method for preparing a porous graphitized carbon carrier loaded with a platinum-based catalyst
By using green and environmentally friendly soluble polymer materials and specific process treatments, porous graphitized carbon carriers with high graphitization and rich pore structures were prepared, which solved the problem of corrosion and limited pore structure formation in traditional carbon carriers under high potentials. The activity and stability of fuel cell catalysts have been significantly improved.
Patent Information
- Application Number
- CN202411255252.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-09-09
AI Technical Summary
Among the existing fuel cell catalysts, the carbon support of traditional carbon black materials is prone to corrosion under high potential conditions, and the pore structure formation is limited, making it difficult to have the characteristics of high graphitization and rich pore structure, which affects the reactivity of the catalyst and Durability.
Using green and environmentally friendly soluble polymer materials as carbon support precursors, platinum-based catalyst particles are designed to grow in situ and disperse in porous carbon support through gelation treatment, segmented heat treatment and pickling processes to form highly graphitized porous graphitized carbon carrier with rich pore structure and hydrophilicity.
It significantly improves the catalytic activity and stability of the catalyst, improves the graphitization degree and pore structure richness of the carbon support, and enhances the reaction performance of the material.
Smart Images

Figure CN118763240B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fuel cell catalysts and relates to a method for preparing a porous graphitized carbon carrier-loaded platinum-based catalyst. Background Art
[0002] For fuel cell catalysts, the crystal structure, pore structure and surface functional groups of the carbon carrier play an important role in the reaction activity and durability of the supported precious metal catalyst. Commonly used carbon carriers include carbon black, Ketjen black, acetylene black, carbon tubes, graphene, carbon fibers, etc. Non-graphitized carbon carriers are prone to corrosion under harsh conditions such as high potential conditions in fuel cell systems, while graphitized carbon carriers usually have disadvantages such as low specific surface area and low dispersion. Therefore, the development of carbon carriers with advantages such as high graphitization and rich pore structure is one of the key research contents in the development of new fuel cell catalysts.
[0003] After searching the relevant patents, it was found that patent CN113506885B discloses a graphitized carbon carrier for hydrogen fuel cells, a preparation method and a preparation method of its battery catalyst, and further improves the uniformity of the catalytic graphitization degree on the surface of the carbon carrier by adding additives. However, the selected additives are ethylenediamine, aniline, polyvinylpyrrolidone, ethylenediaminetetraacetic acid, pyrrole, pyridine, etc., and the environmental friendliness of the above materials is relatively poor. Patent CN115611274 A provides a method for rapid graphitization of porous carbon materials, which fully impregnates carbon materials such as catalysts and porous carbon, and then uses ultra-fast Joule heating after drying, and then pickles to remove metal particles to obtain a highly graphitized carbon carrier.
[0004] The technologies disclosed in the above two patents use traditional carbon black materials as the carbon carrier, which limits the formation of the pore structure of the carbon carrier. In view of this, the present invention proposes a method of using green and environmentally friendly soluble polymer materials as carbon carrier precursors. Through gelation treatment, heat treatment, acid washing and other process designs, platinum-based catalyst particles will grow in situ and disperse in the porous carbon carrier. The porous graphitized carbon carrier designed and prepared by the present invention can have the advantages of high graphitization degree, rich pore structure, strong hydrophilicity, etc. Summary of the invention
[0005] The object of the present invention is to provide a method for preparing a porous graphitized carbon carrier loaded with a platinum-based catalyst, which has the characteristics of high graphitization degree, rich pore structure and strong hydrophilicity.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] A method for preparing a porous graphitized carbon carrier-supported platinum-based catalyst, the preparation method process is as follows:
[0008] S1: Mix the water-soluble polymer material composed of carbon, hydrogen and oxygen elements with the transition metal salt in a mass ratio of (0.8-5):1, and evenly disperse them in 500-600 ml of deionized water;
[0009] S2: Add 20% by mass of an inorganic alkaline solution to the solution prepared in S1, adjust the pH value to 9-9.5, heat to 80-100°C, perform gelation treatment for 12-24 hours, wash the obtained gel with deionized water, dry at 110°C for 24 hours, grind the dried solid to obtain a mixture A;
[0010] S3: The mixture A obtained in S2 is transferred into a heat treatment device in an argon atmosphere, and the mixture A is subjected to a staged heat treatment to obtain a mixture B. The specific process of the staged heat treatment is as follows:
[0011] The first stage of thermal decomposition is carried out, heating from room temperature to 400-600℃ for 2-5h, and the heating rate is controlled at 2-3℃ / min;
[0012] Then, the second stage of catalytic graphitization heat treatment is carried out, the temperature is raised to 1000-1400°C for heat treatment for 5-8h, and the heating rate is controlled at 8-10°C / min;
[0013] S4: The mixture B obtained in S3 is pickled with an acid solution, heated to 60-90° C., and the pickling time is 24-72 hours to obtain a porous carbon support composite material C;
[0014] S5: Add an aqueous solution containing platinum ions and transition metal ions into 500 ml of a 20% by mass composite material C dispersion for standing treatment, wherein the stoichiometric ratio of platinum ions and transition metal ions is (2~5):1, and the standing time is 12 hours. After drying, the above mixture is transferred into a hydrogen atmosphere for heat treatment at a treatment temperature of 1000°C and a treatment time of 2~3 hours to obtain the catalyst.
[0015] Furthermore, the water-soluble polymer material composed of carbon, hydrogen and oxygen elements in S1 is one or more of carboxymethyl cellulose, cyclodextrin and water-soluble starch.
[0016] Furthermore, the transition metal in S1 is one or more of cobalt, nickel, manganese, iron, aluminum, titanium, chromium, tungsten, yttrium and lanthanum.
[0017] Furthermore, the inorganic alkaline solution in S2 is one or more of sodium carbonate, potassium carbonate, sodium hydroxide, and potassium hydroxide.
[0018] Furthermore, the acid solution in S4 is one or more of hydrochloric acid, sulfuric acid, nitric acid, and glacial acetic acid.
[0019] Furthermore, the concentration of the acid solution in S4 is 1-3M.
[0020] Furthermore, the platinum ions in S5 are one or more of chloroplatinic acid, sodium chloroplatinate, and potassium chloroplatinate.
[0021] Furthermore, the specific surface area of the porous carbon support in the catalyst in S5 is 750-800 m 2 / g.
[0022] The present invention uses gelation treatment combined with segmented heat treatment. Combining the two methods can provide more detailed adjustment for the performance of the material.
[0023] Through gelation treatment, the transition metal ions are fully chemically adsorbed mainly through chemical bonds, and a supporting network for the transition metal is formed through a chemical cross-linking process, thereby ensuring the uniform dispersion of the transition metal elements on its surface and inside; the segmented heat treatment is mainly achieved through (1) slow low-temperature thermal decomposition to achieve the carbonization process and ensure that the transition metal elements are deposited in situ on the surface of the obtained carbon material; through (2) catalytic graphitization, high-temperature heat treatment above 1000°C is used to improve the crystallinity of the carbon material, without relying on other graphitization processes (2000°C high-cost and complex processes).
[0024] Beneficial effects of the present invention:
[0025] The present invention proposes a method of using a green and environmentally friendly soluble polymer material as a carbon carrier precursor. Through gelation treatment, heat treatment, acid washing and other process designs, platinum-based catalyst particles will be in-situ grown and dispersed in a porous carbon carrier. The porous graphitized carbon carrier designed and prepared by the present invention can have the advantages of high graphitization degree, rich pore structure, strong hydrophilicity and the like; the platinum-based catalyst loaded on the porous graphitized carbon carrier prepared by the present invention can effectively improve the catalytic activity and stability of the catalyst material. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to facilitate understanding by those skilled in the art, the present invention is further described below with reference to the accompanying drawings.
[0027] Figure 1 TEM images of a carbon support loaded with cobalt oxide and b porous graphitized carbon support prepared in Example 1;
[0028] Figure 2 This is the crystalline structure of the carbon support prepared in Example 1. DETAILED DESCRIPTION
[0029] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in conjunction with the accompanying drawings and preferred embodiments.
[0030] Example 1
[0031] S1: Mix 10 g of water-soluble starch and 2.0 g of cobalt chloride hexahydrate and evenly disperse them in 500 ml of deionized water;
[0032] S2: Add 20% by mass sodium hydroxide solution to the solution prepared in S1, adjust the pH value to 9-9.5, heat to 100°C, perform gelation treatment for 12 hours, wash the obtained gel with deionized water, dry at 110°C for 24 hours, grind the dried solid to obtain a mixture A;
[0033] S3: The mixture A obtained in S2 is transferred into a heat treatment device in an argon atmosphere, and the mixture A is subjected to a staged heat treatment to obtain a mixture B. The specific process of the staged heat treatment is as follows:
[0034] The first stage of thermal decomposition was carried out by heating from room temperature to 500 °C for 2 h, and the heating rate was controlled at 3 °C / min;
[0035] Then the second stage of catalytic graphitization heat treatment was carried out, the temperature was raised to 1400°C for heat treatment for 5h, and the heating rate was controlled at 10°C / min;
[0036] S4: The mixture B obtained in S3 is pickled with a sulfuric acid solution having a molar concentration of 2.5 M, heated to 90° C., and the pickling time is 24 h to obtain a porous carbon support composite material C;
[0037] S5: Add an aqueous solution of chloroplatinic acid and cobalt acetate to 500 ml of a 20% composite material C dispersion according to a stoichiometric ratio of 2:1 and place the mixture in a hydrogen atmosphere for heat treatment at 900°C for 2 hours to obtain the catalyst. The platinum-cobalt alloy catalyst particles will grow in situ and disperse in the porous carbon carrier, and the specific surface area of the porous carbon carrier is 800 m 2 / g.
[0038] In the PtCo / C catalyst prepared in Example 1, platinum-cobalt alloy particles are dispersed in a porous carbon support, and the average particle size is ~5 nm. RDE shows that the mass specific activity of the catalyst at a voltage of 0.9 V is 0.35 A / mg. Pt, MEA battery test shows that at 2000mA / cm 2When tested at a current density of 1.50 Å, the initial voltage was above 0.63 V, the ECSA Loss % (0.6 V - 0.9 V, 30 k square wave) was less than 40%, and the catalytic mass activity attenuation (between 1.0 V - 1.5 V, 5 k triangle wave) was less than 40%.
[0039] Figure 1 TEM images of a carbon support loaded with cobalt oxide and b porous graphitized carbon support prepared in Example 1 show that the carbon support has a rich pore structure after the cobalt oxide is etched. Figure 2 As shown, the crystal structure of the carbon carrier is clear, which is different from the crystal structure of carbon black, confirming that the carbon carrier designed in the present invention has the advantages of high graphitization degree and rich pore structure.
[0040] Example 2
[0041] S1: Mix 15g of cyclodextrin and 5g of ferric chloride hexahydrate and evenly disperse them in 600ml of deionized water;
[0042] S2: Add 20% sodium carbonate solution by mass to the solution prepared in S1, adjust the pH value to 9-9.5, heat to 90°C, perform gelation treatment for 24 hours, wash the obtained gel with deionized water, dry at 110°C for 24 hours, grind the dried solid to obtain a mixture A;
[0043] S3: The mixture A obtained in S2 is transferred into a heat treatment device in an argon atmosphere, and the mixture A is subjected to a staged heat treatment to obtain a mixture B. The specific process of the staged heat treatment is as follows:
[0044] The first stage of thermal decomposition was carried out, with the temperature rising from room temperature to 600 °C for 3 h, and the heating rate was controlled at 2 °C / min;
[0045] Then the second stage of catalytic graphitization heat treatment was carried out, the temperature was raised to 1200°C for 8h, and the heating rate was controlled at 8°C / min;
[0046] S4: The mixture B obtained in S3 is pickled with a hydrochloric acid solution having a molar concentration of 3M, heated to 60° C., and the pickling time is 72 hours to obtain a porous carbon support composite material C;
[0047] S5: Add an aqueous solution of chloroplatinic acid and cobalt acetate to 500 ml of a 20% composite material C dispersion according to a stoichiometric ratio of 4:1 for a standing treatment for 12 hours. After drying, the mixture is transferred into a hydrogen atmosphere for heat treatment at a temperature of 900°C for 3 hours to obtain the catalyst. The platinum-cobalt alloy catalyst particles are in-situ grown and dispersed in the porous carbon carrier, and the specific surface area of the porous carbon carrier is 800 m 2 / g.
[0048] In the PtCo / C catalyst prepared in Example 2, platinum-cobalt alloy particles are dispersed in a porous carbon support, and the average particle size is about 6 nm. RDE shows that the mass specific activity of the catalyst at a voltage of 0.9 V is 0.32 A / mg. Pt , MEA battery test shows that at 2000mA / cm 2 When tested at a current density of 1.50 Å, the initial voltage was above 0.62 V, the ECSA Loss % (0.6 V - 0.9 V, 30 k square wave) was less than 45%, and the catalytic mass activity attenuation (between 1.0 V - 1.5 V, 5 k triangle wave) was less than 45%.
[0049] Example 3
[0050] S1: Mix 5g of carboxymethyl cellulose and 6g of nickel chloride hexahydrate and evenly disperse them in 500ml of deionized water;
[0051] S2: Add 20% by mass potassium hydroxide solution to the solution prepared in S1, adjust the pH value to 9-9.5, heat to 80°C, perform gelation treatment for 12 hours, wash the obtained gel with deionized water, dry at 110°C for 24 hours, grind the dried solid to obtain a mixture A;
[0052] S3: The mixture A obtained in S2 is transferred into a heat treatment device in an argon atmosphere, and the mixture A is subjected to a staged heat treatment to obtain a mixture B. The specific process of the staged heat treatment is as follows:
[0053] The first stage of thermal decomposition was carried out by heating from room temperature to 400 °C for 5 h, and the heating rate was controlled at 2 °C / min;
[0054] Then the second stage of catalytic graphitization heat treatment was carried out, the temperature was raised to 1000°C for 6 hours, and the heating rate was controlled at 8°C / min;
[0055] S4: The mixture B obtained in S3 is pickled with a sulfuric acid solution having a molar concentration of 1 M, heated to 80° C., and the pickling time is 72 h to obtain a porous carbon support composite material C;
[0056] S5: Add an aqueous solution of chloroplatinic acid and nickel chloride to 500 ml of a 20% composite material C dispersion according to a stoichiometric ratio of 5:1 and place the mixture in a standing position for 12 hours. After drying, transfer the mixture into a hydrogen atmosphere for heat treatment at a temperature of 800°C for 3 hours to obtain the catalyst. The platinum-cobalt alloy catalyst particles will grow in situ and disperse in the porous carbon carrier, and the specific surface area of the porous carbon carrier is 750 m 2 / g.
[0057] In the PtNi / C catalyst prepared in Example 3, platinum-nickel alloy particles are dispersed in a porous carbon support, with an average particle size of ~5.5 nm. RDE shows that the mass specific activity of the catalyst at a voltage of 0.9 V is 0.30 A / mg. Pt , MEA battery test shows that at 2000mA / cm 2 When tested under a current density of 2.5 Å, the initial voltage was above 0.63 V, the ECSA Loss % (0.6 V - 0.9 V, 30 k square wave) was less than 48%, and the catalytic mass activity attenuation (between 1.0 V and 1.5 V, 5 k triangle wave) was less than 47%.
[0058] Comparative Example 1:
[0059] S1: Mix 10 g of water-soluble starch and 2.0 g of cobalt chloride hexahydrate and evenly disperse them in 500 ml of deionized water;
[0060] S2: Add 20% by mass sodium hydroxide solution to the solution prepared in S1, adjust the pH value to 9-9.5, wash with deionized water, dry at 60°C for 12h, grind the dried solid to obtain a mixture A;
[0061] S3: The mixture A obtained in S2 is transferred into a heat treatment device in an argon atmosphere, and the mixture A is subjected to a staged heat treatment to obtain a mixture B. The specific heat treatment process is as follows:
[0062] Heat treatment at 600℃ for 5h, heating rate controlled at 10℃ / min;
[0063] The remaining steps are the same as in Example 1.
[0064] Compared with Example 1, it can be clearly seen that the platinum particles in Example 1 are unevenly distributed, and the average particle size is greater than 7nm, which does not achieve the expected effect. The carbon carrier obtained has a low degree of graphitization and a specific surface area of 500m 2 / g.
[0065] In the PtCo / C catalyst prepared in Comparative Example 1, RDE showed that the mass specific activity of the catalyst at a voltage of 0.9 V was 0.22 A / mg. Pt,MEA battery test shows that at 2000mA / cm 2 When tested under a current density of 2.50 Å, the initial voltage was above 0.60 V, the ECSA Loss % (0.6 V - 0.9 V, 30 k square wave) was less than 60%, and the catalytic mass activity attenuation amplitude (between 1.0 V - 1.5 V, 5 k triangle wave) was less than 60%.
[0066] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a porous graphitized carbon carrier-supported platinum-based catalyst, characterized in that: The preparation method process is as follows: S1: Mix the water-soluble polymer material composed of carbon, hydrogen and oxygen elements with the transition metal salt in a mass ratio of (0.8-5):1, and evenly disperse them in 500-600 ml of deionized water; Wherein, the water-soluble polymer material composed of carbon, hydrogen and oxygen elements is one or more of carboxymethyl cellulose, cyclodextrin and water-soluble starch; S2: Add 20% by mass of an inorganic alkaline solution to the solution prepared in S1, adjust the pH value to 9-9.5, heat to 80-100°C, perform gelation treatment for 12-24 hours, wash the obtained gel with deionized water, dry at 110°C for 24 hours, grind the dried solid to obtain a mixture A; Wherein, the inorganic alkaline solution is one or more of sodium carbonate, potassium carbonate, sodium hydroxide, and potassium hydroxide; S3: The mixture A obtained in S2 is transferred into a heat treatment device in an argon atmosphere, and the mixture A is subjected to a staged heat treatment to obtain a mixture B. The specific process of the staged heat treatment is as follows: The first stage of thermal decomposition is carried out, heating from room temperature to 400-600℃ for 2-5h, and the heating rate is controlled at 2-3℃ / min; Then, the second stage of catalytic graphitization heat treatment is carried out, the temperature is raised to 1000-1400°C for heat treatment for 5-8h, and the heating rate is controlled at 8-10°C / min; S4: The mixture B obtained in S3 is pickled with an acid solution, heated to 60-90° C., and the pickling time is 24-72 hours to obtain a porous carbon support composite material C; S5: Add an aqueous solution containing platinum ions and transition metal ions into 500 ml of a 20% by mass composite material C dispersion for standing treatment, wherein the stoichiometric ratio of platinum ions and transition metal ions is (2~5):1, and the standing time is 12 hours. After drying, transfer the mixture into a hydrogen atmosphere for heat treatment at a treatment temperature of 900°C for a treatment time of 2~3 hours to obtain the catalyst.
2. The method for preparing a porous graphitized carbon carrier-supported platinum-based catalyst according to claim 1, characterized in that: The transition metal in S1 is one or more of cobalt, nickel, manganese, iron, aluminum, titanium, chromium, tungsten, yttrium and lanthanum.
3. The method for preparing a porous graphitized carbon carrier-supported platinum-based catalyst according to claim 1, characterized in that: The acid solution in S4 is one or more of hydrochloric acid, sulfuric acid, nitric acid, and glacial acetic acid.
4. The method for preparing a porous graphitized carbon carrier-supported platinum-based catalyst according to claim 1, characterized in that: The concentration of the acid solution in S4 is 1-3M.
5. The method for preparing a porous graphitized carbon carrier-supported platinum-based catalyst according to claim 1, characterized in that: The platinum ions in S5 are one or more of chloroplatinic acid, sodium chloroplatinate, and potassium chloroplatinate.
6. The method for preparing a porous graphitized carbon carrier-supported platinum-based catalyst according to claim 1, characterized in that: The specific surface area of the porous carbon support in the catalyst of S5 is 750-800 m 2 / g.
Citation Information
Patent Citations
A graphitized carbon support for hydrogen fuel cells, its preparation method, and its battery catalyst.
CN113506885B
Method for rapidly graphitizing porous carbon material and application thereof
CN115611274A
Preparation method of mesoporous carbon nano composite catalytic material simultaneously loaded with transition metal monatomic and metallic nanoparticles
CN115722242A
Preparation method of hierarchical-pore nitrogen-doped graphitized carbon-loaded platinum-based catalyst
CN117352760A
Cited By
Preparation method and application of proton exchange membrane fuel cell catalyst
CN121839726A